Application of accounting outsourcing as a business strategy of the enterprise in a pandemic - I.R.; S.M. (Економіка, управління та адміністрування, 2022)
The article considers the use of accounting outsourcing services during the spread of coronavirus disease. It is emphasized that the outsourcing of accounting services is modern and necessary in the pandemic business strategy of the company in both short and long term. The prospects of using accounting outsourcing at domestic enterprises during the global crisis are identified and characterized, such as: business continuity, strategic planning and development, expansion and optimization of activities, application of modern technologies, professionalism of services, cost reduction. The global crisis has accelerated the processes of automation and digitalization in domestic enterprises and has shown a growing need for the introduction of information and communication technologies. It is recommended that outsourcers initiate a review of service contracts in terms of changes in contract terms and conditions, price structure, supply model and scope of services. In turn, in a pandemic, outsourcing customers should stipulate in the contracts that the outsourcing company assumes most of the risks, especially to maintain business continuity.